Geographic variation in liver transplantation persists despite implementation of Share35. Issue 4 (30th August 2017) - Stine, Jonathan G.; Northup, Patrick G.; Stukenborg, George J.; Cornella, Scott L.; Maluf, Daniel G.; Pelletier, Shawn J.; Argo, Curtis K.
Abstract : Aim: Geographic disparities persist in the USA despite locoregional organ sharing policies. The impact of national organ sharing policies on waiting‐list mortality on a regional basis remains unknown. Methods: Data on all adult liver transplants between 1 February 2002 and 31 March 2015 were obtained from the United Network for Organ Sharing/Organ and Transplantation Network. Multivariable Cox proportional hazards models were constructed in a time‐to‐event analysis to estimate waiting‐list mortality for the pre‐ and post‐Share35 eras. Results: In the analyzed time period, 134 247 patients were listed for transplantation and 54 510 received organs (42.8%). Listing volume increased following the introduction of the Share35 organ sharing policy (15 976 candidates pre‐ vs. 18 375 post) without significant regional changes as did the number of transplants (7210 pre‐ vs. 8224 post). Waiting‐list mortality improved from 12.2% to 8.1% ( P < 0.001). Adjusted waiting‐list mortality ratios remained geographically disparate. Region 10 and region 11 had lower hazard ratios (HR) but still had increased mortality (1.46, 95% confidence interval [CI] 1.34–1.60, P < 0.001; and HR 1.49, 95% CI 1.37–1.62, P < 0.001, respectively). Regions 3 and 6 had increased HR with persistently elevated waiting‐list mortality (1.79, 95% CI 1.66–1.93, P < 0.001; and HR 1.29, 95% CI 1.16–1.45, P < 0.001, respectively). Model for End‐state Liver Disease (MELD) exception continued to propagate a survival benefit (HR 0.65, 95% CI 0.63–0.68, P < 0.001). Conclusions: Although overall waiting‐list mortality has decreased, geographic disparities persist, but appear reduced despite broader sharing policies enacted by Share35. The advantage afforded by MELD exception, while still present, was diminished by Share35 as organs are being shifted to MELD >35 candidates. The disparities highlighted by our findings imply a need to review current allocation policies to best balance local, regional, and national transplant environments.